Dual HER-OER performance during alkaline water splitting found in CrMnFeCo-based high-entropy materials - Somdee, Siriwimol; Saelee, Tinnakorn; Khajondetchairit, Patcharaporn; Ektarawong, Annop; Kheawhom, Soorathep; Alling, Bjӧrn; Praserthdam, Piyasan; Rittiruam, Meena; Praserthdam, Supareak (My University, 2026)
The development of high-efficiency electrocatalyst for hydrogen production via electrochemical water splitting is crucial for advancing renewable energy technologies. However, the sluggish kinetics of hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) remain significant challenges. In this study, CrMnFeCoX high-entropy materials (HEMs; X = Cu, Ga, P, and Zn) are investigated as electrocatalysts for overall water splitting in alkaline media using density functional theory calculations. These HEMs are modeled using the special quasi-random structure method with a face-centered cubic (111) structure. The results revealed that the OER activity cannot be sustained due to strong adsorption of oxygenated intermediates. Specifically, the dissociation of the O-O bond in the *OOH intermediate leads to surface oxidation, which decreases activity, evidenced by the d ( p )-band center shift. Consequently, HER activity is analyzed on pristine surfaces, whereas OER activity is evaluated on oxide surfaces. The CrMnFeCoCu surface exhibits excellent HER activity, achieving a low overpotential of 0.03 V vs. RHE, attributed to effective water dissociation and moderate *H adsorption energies. Meanwhile, the CrMnFeCoP surface demonstrates superior OER activity with an overpotential of 0.39 V vs. RHE, driven by its moderate adsorption energies for oxygenated intermediates. Site-specific analyses identify Cu and Co as the primary active sites for HER and OER, respectively. These findings highlight CrMnFeCoCu and CrMnFeCoP as promising candidates for the rational design of efficient electrocatalysts for HER and OER in electrochemical water splitting.
Keywords: Density functional theory; High-entropy alloys; Hydrogen; Water oxidation